The Theory of Domestic Content Protection and Content Preference - Grossman, Gene M. (Quarterly Journal of Economics, 1981)
This paper investigates the resource reallocation effected by content protection and content preference schemes under alternative assumptions regarding the definition of domestic content, the number of intermediate goods, and the market structure of the domestic intermediate good industry. Content protection is shown to be equivalent to a combination of more familiar commercial policies. However, the extent of application of these policies is determined endogenously by parameters of the production functions for intermediate and final goods. A number of anomalous and undesirable outcomes that may result from content protection and content preference are discussed.